Genetic testing and Guangdong college students in China: A cross-sectional study of knowledge and attitudes - Jiaming Wang; Ruoru Lin; Sijing Luo; Beilei Zhong; Yuran Zhu; Jiayi Huang; Dangui Zhang; William Ba-Thein (Preventive Medicine Reports)
Objective: This study investigated functional health literacy and attitudes toward genetic testing among Chinese college students to understand if they can make informed decisions and avoid potential risks. Methods: A cross-sectional anonymous online survey was conducted with students from 13 colleges in Guangdong province during October–November 2021. Results: Of the 1543 participants, 53.9 % were female, predominantly undergraduates (97.2 %). Most students reported being health-conscious (76.6 %), less religious (60.3 %), possessing health esteem (76.4 %), and having parents in non-healthcare occupations (89.1 %). The median score for functional genetic literacy was 10 out of 17. Most (91.4 %) expressed positive attitudes toward genetic testing, with 65.1 % favoring direct-to-consumer options. The most preferred tests were predictive (83.3 %) and premarital/preconception tests (76.4 %). Multiple linear regression analysis showed independent predictors of functional genetic literacy as female gender (Beta, 95 %CI: 0.26, 0.02–0.49), medicine major (1.51, 1.27–1.74), health-esteem personality trait (0.34, 0.06–0.62), lower religiosity (0.66, 0.49–0.83), and lower perceived financial status (0.47, 0.21–0.73). Logistic regression analysis identified independent predictors of positive attitude toward genetic testing as self-respect personality (adjusted odds ratio, 95 %CI: 1.81, 1.23–2.66), lower perceived financial status (0.57, 0.38–0.83), and parental occupation in non-healthcare (0.38, 0.17–0.89). Conclusions: Guangdong college students were mostly positive toward genetic testing, particularly predictive and premarital options. However, their limited functional genetic testing literacy may hinder informed decision-making. To address ethical, legal, and social implications, China should strengthen public education, promote the genetic counseling profession and enhance regulatory oversight in the genetic testing industry.